Esclarecimento, semiformação e a liquidação do indivíduo - Junkes, Delcio (Universidade Federal de São Carlos, 2008)
The project of enlightenment (Aufklärung) was to disenchant the world, replacing the myths and the imagination by the knowledge. This process is essential for the human being can achieve the autonomy. But instead of conducting the individual to autonomy, as it was thought in the Illuminist project, the enlightenment disembogued into a process of semi-formation that causes the loss of identity and cancellation of the individual, approaching humanity to a totalitarian system. As Adorno and Horkheimer said at the preface of the Dialectic of Enlightenment: "Not harbour any doubt - and so our petitio principii lies - that the freedom in society is inseparable from thinking enlightenment." The progress of rational enlightenment over its development process is gradually creating serious obstacles to the construction of autonomy, or even denying this possibility, when giving priority only to the technical and scientific aspects of the reason (instrumental reason). This is due in large part to the action of the cultural industry, officer semi-formation. The intention of this work, which has its theoretical foundation in the philosophy of Critical theory, especially in the thought of Theodor Adorno, is to search in culture and art the elements that could annul the semi-formation, and help in the construction of identity and autonomy of individuals, rescuing the potential and emancipating of the enlightenment.
Keywords: Teoria crítica; Dialética do esclarecimento; Semiformação; Emancipação política; Indústria cultural; Esclarecimento; Progresso; Critical theory; Semi-formation; Enlightenment; Progress; CIENCIAS HUMANAS::FILOSOFIA